Pemanfaatan Taman Baca Untuk Meningkatkan Kemampuan Literasi Anak Usia Sekolah Dasar - Hasbahuddin, Hasbahuddin; Irmawati, Irmawati; Hutapea, Bilferi (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to carry out renovations and revitalization of the "SB Allo Simbar" reading garden to improve the literacy skills of elementary school-age children. The method of implementing activities includes stages; Stage 1. Preparation; Identification of needs or need-assessment, Renovation of SB Allo Simbar Reading Gardens, Procurement of reading materials, and Recruitment or selection of environment-based Reading Park administrators. Stage 2. Training of reading administrators. Stage 3. Evaluation and follow-up plans. Stage 4 Final Goal or Goal. Furthermore, the results of the activity can be concluded that the Allo Simbar Reading House activity program can improve literacy skills in elementary school-age children in the Tundaq environment, Laburan Utara Village, Banggae Timur District, Majene Regency.